The Effect of Flushing Premating with Spirulina Platensis Supplementation on Ewes Postpartum Estrus - Diahanvika Tri Sarvinda; Sigit Bintara; I Gede Suparta Budisatria; Kustantinah Kustantinah; Endang Baliarti (Buletin Peternakan, 2022)
Lactating ewes require high nutrients for basic life requirements and milk production. If not fulfilled, it can have an impact on Negative Energy Balance (NEB) that reduces body weight, Body Condition Score (BCS), and extend the appearance of Postpartum Estrus (PPE). Premating flushing feed is an effort to improve ewe nutrients by adding high nutrition for preparation before mating so that after lambing and suckling, the ewe immediately estrus. This research aimed to evaluate the performance of ewes through premating flushing feeding. The research was conducted at Mendo Galak Farm, Sleman, Yogyakarta. Twenty ewes 2-3 years old with BCS 2-3 divided into two groups; the group with flushing treatment consisted of dried water spinach (Ipomoea reptans poir), concentrate feed with Spirulina sp. (14,92% crude protein, 60,28% total digestible nutrients), and the control group (PS) without Spirulina sp. (crude protein 11,82%, total digestible nutrients 53,20%). Flushing feed was given after a month postpartum as much as 3% dry matter of body weight. The recorded parameter was daily feed consumption, monthly body weight, BCS, and postpartum estrus. The data obtained were tested by an independent T-test with Statistical Product and Service Solution (SPPS ver. 22). The results showed the consumption and digestibility of CP, TDN, and ewe's ADG had a significant difference (P<0.05).  Postpartum estrus (PPE) of flushed ewes had no significant difference (P>0.05), 73.90±11.55 vs. 77.60±14.65 days, respectively. The conclusion was that flushing premating treatment with the addition of Spirulina platensis increased the nutrient intake and digestibility of CP, TDN, and ADG but had not shortened on postpartum estrus of lactating ewes.